2004
DOI: 10.1017/s0033291704002272
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and negative appraisals in survivors of severe acute respiratory syndrome (SARS)

Abstract: Psychological distress of SARS survivors at 1-month recovery is real and significant. Negative appraisals may play a pivotal role in the development of psychological distress for SARS survivors, at least in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
280
5
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(319 citation statements)
references
References 10 publications
23
280
5
11
Order By: Relevance
“…The results are not surprising as, in addition to the physical impairment, the long period of isolation and extreme uncertainty during the SARS illness had created enormous psychological stress [150] and mood disturbances [151]. Furthermore, steroid toxicity, personal vulnerability and psychosocial stressors might have contributed to the development of psychosis in some patients [152].…”
Section: Long-term Outcomementioning
confidence: 99%
“…The results are not surprising as, in addition to the physical impairment, the long period of isolation and extreme uncertainty during the SARS illness had created enormous psychological stress [150] and mood disturbances [151]. Furthermore, steroid toxicity, personal vulnerability and psychosocial stressors might have contributed to the development of psychosis in some patients [152].…”
Section: Long-term Outcomementioning
confidence: 99%
“…In Hong Kong, hospitalized survivors of SARS were more distressed on average than a matched group of healthy controls from the same geographic area (Chua et al, 2004). Categorical analyses indicated that 35% of the hospitalized SARS survivors in Hong Kong experienced moderate to severe levels of anxiety and depression (Cheng, Wong, Tsang, & Wong, 2004) and that 16% met criteria for depression and 10% for PTSD (Yan, Dun, & Li, 2004). Remarkably, almost as many survivors, 35% of the sample, evidenced a resilient trajectory of stable high mental health.…”
Section: Latent Growth Mixture Modelingmentioning
confidence: 99%
“…Thus, not only did they have to endure highly debilitating symptoms with minimal support, they also had to face the threat of death on their own (Cheng & Wong, 2005). Among those who survived, most suffered from significant psychological distress following one-month recovery (Cheng, Wong, Tsang, & Wong, 2004b;Cheng et al, 2004a). Following short-term physical recovery, SARS survivors were reported to experience significantly higher levels of distress, anxiety and depressive symptoms, as well as a lower quality of life compared to the community and psychiatric samples (Cheng et al, 2004a;Cheng et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Among those who survived, most suffered from significant psychological distress following one-month recovery (Cheng, Wong, Tsang, & Wong, 2004b;Cheng et al, 2004a). Following short-term physical recovery, SARS survivors were reported to experience significantly higher levels of distress, anxiety and depressive symptoms, as well as a lower quality of life compared to the community and psychiatric samples (Cheng et al, 2004a;Cheng et al, 2004b). One year after illness onset, SARS survivors continued to have significant impairment across various quality of life domains compared to their same-age normal controls (Hui et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation